Aggression types and beliefs : a comparison of aggressive and non-aggressive male psychiatric in-patients - De Klerk, Anna Maria Elizabeth (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--University of Stellenbosch, 2000.